Current clinical concepts: integration of psychologically informed practice for management of patients with sport-related injuries - Baez, S.; Jochimsen, K. (Journal of Athletic Training, 2023)
Psychologically informed practice is an approach to patient management that encourages clinicians to treat patients from a biopsychosocial perspective and can be adopted by athletic trainers to manage sport-related injuries. As described in the domains of athletic training clinical practice, athletic trainers are expected to identify, address, and make appropriate referrals regarding psychosocial responses to injuries and mental health symptoms. Psychologically informed practice suggests addressing physical impairments in addition to screening and intervening for psychosocial responses with patients. In this Current Clinical Concepts paper, we discuss appropriate patient-reported outcome measures used to screen for mental health symptoms and psychosocial responses, provide recommendations on psychological interventions that can be integrated to enhance patient outcomes, and describe how to effectively refer a patient to an appropriate mental health professional.